The dual influence path of decent work perception on employee innovative behavior - Yan, Yan; Deng, Di; Geng, Yuqing; Gao, Juan; Lin, Enzhong (Frontiers in Psychology, 2023)
The goal of decent work (DW) is a win-win situation for both employees and employers.It promotes an individual's employability and enhances the competitiveness of the organization.Based on the conservation of resources theory (COR), this paper conducted survey on knowledge workers and analyzed the data by hierarchical linear model (HLM).Research purposes: This paper aims to examine how decent work perception (DWP) influences employee innovation behavior through the mediating effect of job engagement and burnout and the moderating effect of authoritarian leadership.Findings: Based on the results of statistical analyses conducted on 489 valid knowledge workers, it was demonstrated that DWP positively influence employee innovative behavior. Job engagement has a full mediating effect on the relationship between DWP and employee innovative behavior. The study did not support the mediating effect of job burnout, however. There is a positive moderating effect of authoritarian leadership on the relationship between DWP and job engagement and a negative moderating effect on the relationship between DWP and job burnout.In addition to contributing to theoretical studies on DW and work behavior, this paper also contributes to practice on employee motivation and leadership.